A nearly missed foreign body in frontal sinus: case report - Azwan, Nurul Alya Binti; Shanmugam, Ram Kumar Sharma; Teng, Kong Yin (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Foreign body in paranasal sinus is rare. Very few cases have been reported of lodgement of foreign body in paranasal sinuses. Garces and Norris reported that 70% of these foreign bodies usually appeared after maxillofacial traumas and 30% appeared during or after dental procedures of maxilla. Foreign bodies are less common in the frontal sinus as compared to maxillary sinus. This is a case of foreign body in frontal sinus in an eighteen-year-old gentleman after a road traffic accident.